دراسة العلاقة بين البوليبات الأنفية والالتهاب الأنفي الأرجي - الرستم, محمد; الشهابي, زهير; حوراني, حسان (Latakia University Journal -Medical Sciences Series, 2019)
البوليبات الأنفية مرض منتشر في الساحل السوري. قد يكون منشأ البوليبات الأنفية تحسـسياً أو إلتهابياً هدفت هذه الدراسة إلى تحديد العوامل المؤهبة لتشكل البوليبات الأنفية ودور الالتهاب الأنفي الأرجي في ذلك . شملت الدراسة 32 مريضا من مراجعي مشفى الأسد الجامعي والذين أجري لهم استئصال للبوليبات الأنفية وذلك بين عامي 2003 – 2004 أقل من نصف الحالات عزيت للتحسس نسيجياً، بينما وجدت الخلايا المحبة للحمض في المفرزات الأنفية لأكثر من نصف المرضى . اختبار الحساسية الجلدية كان ايجابيا في 7 مرضى فقط, معظم مرضى البوليبات الأنفية يعانون من الانسداد الأنفي بدرجات مختلفة والذي يؤدي لنقص الشم أو حتى لانعدام الشم . Nasal polyps is a prevalent disease in the Syrian coast. The origin of nasal polyps can be either infection or allergic. The aim of this study was to detect The predisposed factors which lead to nasal polyps formation and the role of allergic rhinitis in its etiology. This study includes 32 patients with nasal polyps diagnosed at Al-Assad university hospital in Lattakia. The patients underwent for nasal polypectomy between 2003 – 2004. It was found on histological study that less than half of the cases were due to allergy while the eosinophilic cells were seen in more than half of the cases in the nasal secretions. Prick test was positive only in 7 cases. Most patients with nasal polyps were suffering from nasal obstruction of different severity which may lead to hyposmia or even anosmia.